A new combination in Litsea Lam. (Lauraceae) from north eastern India - Bhuinya, Trina; Singh, Paramjit (Bangladesh Journal of Plant Taxonomy, 2013)
Not available. DOI: http://dx.doi.org/10.3329/bjpt.v20i1.15470 Bangladesh J. Plant Taxon. 20(1): 125-127, 2013 (June)